(untitled) (Plant Tissue Culture and Biotechnology, 2022)
The multiple shoots (14.2) from Oxalis corniculata differentiated through bud breaking on MS medium with 2.0 mg/l BAP. The regenerated shoots were further sub-cultured on MS medium containing 1.0 mg/l BAP and 0.5 mg/l NAA. Vegetative to reproductive phase transition occurred in the cultures affected by plant growth regulators (PGRs), sucrose concentrations, strength of MS salts and light. Flower buds initiated from the regenerated shoots on half strength of MS salts with 1.0 mg/l Kn + 0.5 mg/l NAA and 3% sucrose. These flower buds opened under low light (10-15 μmol m-2 s-1) condition with 18h/6h photoperiod within 3 weeks of culture initiation. The shoots did not flower in the dark. Though smaller in size, the in vitro generated flowers were morphologically comparable to the natural flowers. Fruits were set in the cultures within 5 weeks. Plant Tissue Cult. & Biotech. 32(2): 193-203, 2022 (December)